Peran Rumah Potong Hewan (RPH) Ruminansia Kota Singkawang Dalam Menumbuhkan Jiwa Entrepreneurship Bagi Para Pedagang Hewan Potong Halal - Apriani, Fitri (Eastasouth Institute, 2023)
This research departs from the phenomenon of low public interest in entrepreneurship, this can be seen from the large number of unemployed in Indonesia. RPH Ruminants in Singkawang City seeks to foster an entrepreneurial spirit and create Muslimpreneurs in the halal industry, especially for slaughter animal traders. The role of Singkawang City Ruminant RPH is as a facilitator, regulator and motivator. Supporting factors in fostering an entrepreneurial spirit for halal slaughter animal traders, namely public awareness regarding halal products is already high, consumer interest in halal slaughtered meat is high, entrepreneurship training related to halal slaughter animal products is enthusiastically welcomed by the people in Singkawang City, especially for animal traders Cut both beef and chicken. While the inhibiting factors in fostering an entrepreneurial spirit are the lack of public knowledge about the meaning of halal itself, especially in terms of production and animal welfare, lack of public interest in entrepreneurship.